Evaluation of probiotics' efficiency on cariogenic bacteria: randomized controlled clinical study - Didem Sakaryalı Uyar; Aylin Üsküdar Güçlü; Ekin Çelik; Betül Memiş Özgül; Aylin Altay Koçak; Ahmet Celal Başustaoğlu (BMC, 2024)
Abstract Background Probiotics are live beneficial bacteria to human health and their efficiency on oral health is still being investigated. The purpose of this study was to evaluate the level of Streptococcus mutans and Lactobacillus species with and without the use of probiotics for six-months after the treatment of all dental caries under general anesthesia. Methods Fifty-eight pediatric patients without any systemic diseases, whose dental treatments were completed under general anesthesia (GA), were included in the study. The patients were recruited in two-groups; Group A: Patients started using probiotics after GA and Group B: Patients did not use probiotics after GA. Saliva samples were taken from all patients on the day before GA (T0), at one-month (T1), three-month (T2) and six-month (T3) follow-up after GA. The counts of cariogenic bacteria were determined by the analysis of saliva samples using real-time polymerase chain reaction. Statistical significance level was accepted as p < 0.05. Results There was statistically significant difference between Group A and B for T0, T1, T2 and T3 regarding S. mutans (p = 0.001, p = 0.04, p = 0.04, p = 0.03; p < 0.05). However, there was no statistically significant difference between groups regarding Lactobacillus species (p ≥ 0.05). Conclusions Probiotic use and treatment of all caries significantly reduced the level of S. mutans but not Lactobacillus species. Furthermore, S. mutans decreased after cessation of probiotics, but it was not statistically significant. Trial registration Study was registered as "Effects of Probiotics on Streptococcus mutans and Lactobacillus species" with the registration number of NCT05859646 (16/05/2023) at https://www.clinicaltrials.gov Protocol Registration and Results System.